2022
DOI: 10.1101/2022.10.07.511216
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemoproteomics-guided development of SLC15A4 inhibitors with anti-inflammatory activity

Abstract: SLC15A4 is an endolysosome-resident transporter that is intimately linked with autoinflammation and autoimmunity. Specifically, SLC15A4 is critical for Toll-like receptor (TLR) 7, 8, and 9 as well as the nucleotide-binding oligomerization domain-containing protein (NOD) 2 signaling in several immune cell subsets. Notably, SLC15A4 is essential for the development of systemic lupus erythematosus in murine models and is associated with autoimmune conditions in humans. Despite its therapeutic potential, to our kno… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In line with this, IRF5-deficient mice show strong protection in a broad range of SLE disease models [49][50][51][52][53][54] . These evidences and the fact that solute carriers are an eminently druggable class of proteins, have put forward SLC15A4 as an attractive drug target for SLE and related diseases [55][56][57] . Further supporting this notion, here we show that the SLC15A4-TASL complex is essential for IRF5 activation not only in monocytes and pDCs, but also in human B cells, demonstrating therefore its general requirement in all the endolysosomal TLRresponding cells shown to be critically involved in SLE pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, IRF5-deficient mice show strong protection in a broad range of SLE disease models [49][50][51][52][53][54] . These evidences and the fact that solute carriers are an eminently druggable class of proteins, have put forward SLC15A4 as an attractive drug target for SLE and related diseases [55][56][57] . Further supporting this notion, here we show that the SLC15A4-TASL complex is essential for IRF5 activation not only in monocytes and pDCs, but also in human B cells, demonstrating therefore its general requirement in all the endolysosomal TLRresponding cells shown to be critically involved in SLE pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested SLC15A4 as a potential therapeutic target for systemic lupus erythematosus (SLE) and other autoimmune diseases [21, 38, 44]. In mouse models, the absence of SLC15A4 has been shown to confer resistance to the development of multiple autoimmune diseases, including dextran sulfate sodium (DSS)-induced colitis (wherein Slc15a4 -/- pDCs fail to produce IFNα upon TLR7 agonist R848 stimulation) and the Faslpr model of SLE [18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PHT1 plays a central role in SLE pathogenesis [18][19][20][21][22]. Thus, major efforts are currently underway to identify molecules capable of modulating PHT1 function as strategy for the treatment of diseases associated with altered innate immune responses [47,48]. Despite the obvious interest of PHT1 as drug target, pharmacological development of PHT1 has been limited by the lack of appropriate functional assays and scarce structural information.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the obvious interest of PHT1 as drug target, pharmacological development of PHT1 has been limited by the lack of appropriate functional assays and scarce structural information. Therefore, it is expected that the SSME-based assay introduced in the present work could serve as a screening platform to identify novel PHT1 modulators or to evaluate the pharmacological activity of newly found modulators [47,48]. Furthermore, this SSME assay can also be used to further characterize the functional properties of PHT1 or to study the impact of medically relevant SNPs [21] on normal PHT1 function, all of which would significantly contribute to a better understanding of its physiological role and therapeutic value as drug target.…”
Section: Discussionmentioning
confidence: 99%